Modification method of calcium carbonate, super-hydrophobic coating and preparation method of super-hydrophobic coating

By modifying calcium carbonate with γ-mercaptopropyltriethoxysilane, the problem of poor compatibility of calcium carbonate in superhydrophobic coating is solved, and the uniform dispersion of modified calcium carbonate in polymer matrix is ​​achieved and the high hydrophobicity and self-cleaning ability of superhydrophobic coating is achieved.

CN119662048APending Publication Date: 2025-03-21CANGZHOU NORMAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411839416.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing superhydrophobic materials are expensive, complex preparation process and long time, and their application range is limited; while calcium carbonate as a filler is difficult to disperse evenly in superhydrophobic coatings due to poor hydrophilicity and compatibility, which affects the performance of composite materials.

Method used

Calcium carbonate was modified by using γ-mercaptopropyltriethoxysilane (KH580) as a modifier. Modified calcium carbonate with excellent hydrophobicity was obtained by mixing calcium carbonate, KH580 and ethanol and adding ammonia water to the modification reaction.

Benefits of technology

The hydrophobicity of modified calcium carbonate is significantly improved, with contact angles up to above 120°; it is evenly dispersed in the polymer matrix, and the contact angle of the prepared superhydrophobic coating can reach above 150°, and has excellent self-cleaning ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662048A_ABST
    Figure CN119662048A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrophobic materials, in particular to a modification method of calcium carbonate, a super-hydrophobic coating and a preparation method of the super-hydrophobic coating. According to the invention, gamma-mercaptopropyltriethoxysilane (silane coupling agent KH580, or KH580 for short) is taken as a modifier, calcium carbonate is modified by adopting a specific modification method, the obtained modified calcium carbonate has excellent hydrophobicity, and the contact angle can reach 120 degrees or more. The contact angle of the prepared super-hydrophobic coating can reach 150 degrees or above by using the nano-silver as the filler, and the super-hydrophobic coating has excellent self-cleaning capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrophobic materials, and in particular to a calcium carbonate modification method, a super hydrophobic coating and a preparation method thereof. Background Art

[0002] Super-hydrophobic materials are widely concerned because they have special properties such as self-cleaning, anti-fouling flashover, anti-corrosion, oil-water separation, but many super-hydrophobic materials are limited in their application range due to reasons such as expensive, complicated preparation process and long time consuming. Calcium carbonate is a kind of cheap, easy to obtain, non-toxic and harmless inorganic powder material, often used in super-hydrophobic coating in the form of filler, it has the advantages of increasing surface roughness, reducing surface energy, reducing super-hydrophobic material price. But calcium carbonate is a hydrophilic substance, and the surface free energy is large. Using calcium carbonate as filler will affect composite material performance because of poor compatibility with polymer matrix, and serious agglomeration, it is difficult to be evenly dispersed in polymer matrix. In order to enhance the compatibility of calcium carbonate with polymer matrix, improve the dispersibility of calcium carbonate inside composite material, it can be surface modified by organic molecules. At present, the method of commonly used modified calcium carbonate mainly contains dry modification, wet modification and in-situ modification, wherein dry modification and wet modification belong to physical modification method, and in-situ modification belongs to chemical method. Since physical methods can make full use of existing calcium carbonate and further reduce costs, they have more industrial application prospects. Compared with dry modification, wet modification has stable effects, less energy consumption and low cost, but the hydrophobicity of calcium carbonate obtained by wet modification still needs to be improved and cannot meet the application fields with high requirements for hydrophobicity. Summary of the invention

[0003] In view of this, the present invention provides a modification method of calcium carbonate, a super hydrophobic coating and a preparation method thereof. The present invention uses γ-mercaptopropyltriethoxysilane (silane coupling agent KH580, or KH580 for short) as a modifier to modify calcium carbonate, and the obtained modified calcium carbonate has excellent hydrophobicity, and the contact angle can reach more than 120°.

[0004] In one aspect, the present invention provides a method for modifying calcium carbonate, comprising the following steps:

[0005] Calcium carbonate, γ-mercaptopropyltriethoxysilane and ethanol are mixed, and then ammonia water is added to carry out a modification reaction to obtain modified calcium carbonate.

[0006] Optionally, the calcium carbonate is at least one of cubic calcium carbonate and rod-shaped calcium carbonate, and the average particle size of the calcium carbonate is 2.5-6.0 μm.

[0007] Optionally, the mass ratio of the calcium carbonate to ethanol is 1:16-18, and the mass of the γ-mercaptopropyltriethoxysilane is 1-5% of the mass of ethanol.

[0008] Optionally, the concentration of the ammonia water is 13-14 mol / L, the mass volume ratio of the calcium carbonate and the ammonia water is 1 g:14-16 mL, and the ammonia water is added at a speed of 1.2-1.8 mL / min.

[0009] Optionally, the modification reaction is carried out at a temperature of 45-55°C and a time of 0.5-2.5h.

[0010] Optionally, after the modification reaction, the process further comprises performing solid-liquid separation on the reaction liquid obtained from the modification reaction, and drying the obtained solid, and the obtained dried solid is the modified calcium carbonate.

[0011] On the other hand, the present invention also provides a super-hydrophobic coating, comprising a polymer matrix and modified calcium carbonate obtained by the modification method described in the above technical solution.

[0012] Optionally, the mass ratio of the modified calcium carbonate to the polymer matrix is ​​2-8:5, and the polymer matrix is ​​polydimethylsiloxane.

[0013] On the other hand, the present invention also provides a method for preparing the super-hydrophobic coating described in the above technical solution, comprising the following steps:

[0014] The modified calcium carbonate, the polymer matrix and the organic solvent are mixed to obtain a mixed solution,

[0015] The mixed solution is formed into a film and then dried to obtain a super hydrophobic coating.

[0016] Optionally, the mass ratio of the polymer matrix to the organic solvent is 1:17-23, and the organic solvent is n-hexane.

[0017] The present invention provides a modification method of calcium carbonate, a super hydrophobic coating and a preparation method thereof. The present invention uses γ-mercaptopropyl triethoxysilane (silane coupling agent KH580, or KH580 for short) as a modifier, and a specific modification method is used to modify calcium carbonate, and the obtained modified calcium carbonate has excellent hydrophobicity, and the contact angle can reach more than 120°. Using it as a filler, the contact angle of the prepared super hydrophobic coating can reach more than 150°, and has excellent self-cleaning ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and other objects, features and advantages of the present invention will be apparent from the following description of preferred embodiments and accompanying drawings which illustrate the subject matter of the present invention and its use, in which:

[0019] Figure 1 It is a comparison diagram of SEM images of cubic calcium carbonate, rod-shaped calcium carbonate, the modified calcium carbonate obtained in Example 4, the modified calcium carbonate obtained in Example 9, and the modified calcium carbonate obtained in Comparative Examples 1-2.

[0020] Figure 2 These are SEM images of cubic calcium carbonate, rod-shaped calcium carbonate and the modified calcium carbonate obtained in Examples 1-10.

[0021] Figure 3 These are SEM images of cubic calcium carbonate, rod-shaped calcium carbonate, the modified calcium carbonate obtained in Example 4, the modified calcium carbonate obtained in Example 9, and the modified calcium carbonate obtained in Examples 11-18.

[0022] Figure 4 The XRD spectra of cubic calcium carbonate, rod-shaped calcium carbonate, the modified calcium carbonate obtained in Example 4, the modified calcium carbonate obtained in Example 9, and the modified calcium carbonate obtained in Comparative Examples 1-2 are shown.

[0023] Figure 5 The infrared spectra of cubic calcium carbonate, rod-shaped calcium carbonate, the modified calcium carbonate obtained in Example 4, the modified calcium carbonate obtained in Example 9 and the modified calcium carbonate obtained in Comparative Examples 1-2 are shown.

[0024] Figure 6 The activation indexes of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 1-10 are shown.

[0025] Figure 7 The activation indexes of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 4, 9 and 11-18 are shown.

[0026] Figure 8 The oil absorption values ​​of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 1-10 are shown.

[0027] Fig. 9 The oil absorption values ​​of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 4, 9 and 11-18 are shown.

[0028] Fig.10 The self-cleaning effect diagrams of the glass slide, the hydrophobic coating obtained in Comparative Example 3, the super-hydrophobic coating obtained in Example 20, and the super-hydrophobic coating obtained in Example 25 are shown. DETAILED DESCRIPTION

[0029] The present invention will be described below by specific embodiments, and it will be appreciated by those skilled in the art that the following specific embodiments are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following embodiments, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following embodiments, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be adopted to process.

[0030] The present invention provides a method for modifying calcium carbonate, comprising the following steps:

[0031] Calcium carbonate, γ-mercaptopropyltriethoxysilane (silane coupling agent KH580) and ethanol are mixed, and then ammonia water is added to carry out a modification reaction to obtain modified calcium carbonate.

[0032] The modified calcium carbonate obtained by the modification method of the present invention has excellent hydrophobicity, and the contact angle can reach more than 120°.

[0033] In some embodiments of the present invention, the calcium carbonate is at least one of cubic calcium carbonate and rod-shaped calcium carbonate. In some embodiments of the present invention, the average particle size of the calcium carbonate is 2.5-6.0 μm, specifically 2.50 μm, 2.75 μm, 3.00 μm, 3.50 μm, 4.00 μm, 5.00 μm, 5.31 μm, 5.70 μm and 6.00 μm. It should be noted that when the calcium carbonate is rod-shaped calcium carbonate, the average particle size refers to the average length.

[0034] In some embodiments of the present invention, the mass ratio of calcium carbonate to ethanol is 1:16-18, specifically 1:16, 1:17 and 1:18, and the mass of γ-mercaptopropyltriethoxysilane is 1-5% of the mass of ethanol, specifically 1%, 2%, 3%, 4% and 5%. In the present invention, the amount of ethanol can ensure that γ-mercaptopropyltriethoxysilane is evenly dispersed in the mixed solution to facilitate the modification reaction.

[0035] In some embodiments of the present invention, the concentration of the ammonia water is 13.0-14.0 mol / L, specifically 13.0 mol / L, 13.4 mol / L and 14.0 mol / L. The present invention does not specifically limit the source of the ammonia water, and commercially available concentrated ammonia water is sufficient. In some embodiments of the present invention, the mass volume ratio of the calcium carbonate to the ammonia water is 1g:14-16mL, specifically 1g:14mL, 1g:15mL and 1g:16mL; the ammonia water is added at a speed of 1.2-1.8mL / min, and the specific addition speed can be 1.2mL / min, 1.3mL / min, 1.4mL / min, 1.5mL / min, 1.6mL / min, 1.7mL / min and 1.8mL / min.

[0036] In some embodiments of the present invention, the temperature of the modification reaction is 45-55°C, specifically 45°C, 50°C and 55°C; the time of the modification reaction is 0.5-2.5h, specifically 0.5h, 1.0h, 1.5h, 2.0h and 2.5h.

[0037] In some embodiments of the present invention, the modification method specifically includes: mixing calcium carbonate, γ-mercaptopropyltriethoxysilane and ethanol, heating the resulting mixed solution to the temperature of the modification reaction, and then adding ammonia water to carry out the modification reaction; wherein the rate of adding ammonia water and the conditions of the modification reaction are as described above and will not be repeated here; the time of the modification reaction is calculated from the time when the ammonia water starts to be added.

[0038] In some embodiments of the present invention, after the modification reaction, the reaction liquid obtained from the modification reaction is further subjected to solid-liquid separation, and the obtained solid is dried, and the obtained dried solid is the modified calcium carbonate.

[0039] The present invention also provides a super-hydrophobic coating, comprising a polymer matrix and modified calcium carbonate obtained by the modification method described in the above technical solution.

[0040] The modified calcium carbonate obtained by the modification method of the present invention is dispersed in a polymer matrix, and the water contact angle of the prepared hydrophobic coating can reach more than 150°, and the coating has excellent self-cleaning ability.

[0041] In some embodiments of the present invention, the mass ratio of the modified calcium carbonate to the polymer matrix is ​​2-8:5, specifically 2:5, 4:5, 6:5 and 8:5. In some embodiments of the present invention, the polymer matrix is ​​polydimethylsiloxane.

[0042] The present invention does not particularly limit the thickness of the super hydrophobic coating, and those skilled in the art can select a suitable thickness according to demand. In an embodiment of the present invention, the thickness of the obtained super hydrophobic coating is about 0.1 mm.

[0043] The present invention also provides a method for preparing the super-hydrophobic coating described in the above technical solution, comprising the following steps:

[0044] The modified calcium carbonate, the polymer matrix and the organic solvent are mixed to obtain a mixed solution,

[0045] The mixed solution is formed into a film and then dried to obtain a super hydrophobic coating.

[0046] In some embodiments of the present invention, the mass ratio of the polymer matrix to the organic solvent is 1:17-23, specifically 1:17, 1:18, 1:19, 1:20, 1:21, 1:22 and 1:23; and the organic solvent is n-hexane.

[0047] The present invention has no particular limitation on the mixing, film-forming and drying methods in the preparation method of super-hydrophobic coating, and the conventional mixing method, film-forming method and drying method in the art can be used. In an embodiment of the present invention, the film-forming method is a dip coating method, that is, the slide is taken out after being immersed in the mixed solution, and a layer of liquid film is formed on the surface of the slide.

[0048] The technical scheme of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and embodiments. The embodiments of the present application are only used as examples, and all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0049] Example 1

[0050] Cubic calcium carbonate (cubic system, average particle size of 2.75 μm, 3 g) and ethanol (50 g) were mixed in a mass ratio of 1:17, and then 1% of the mass of ethanol was added to the silane coupling agent KH-580 to obtain a first mixture. The first mixture was heated to 50°C, and then 15 mL of concentrated ammonia water with a concentration of 13.4 mol / L was added to the first mixture at a rate of 1.5 mL / min to carry out a modification reaction for 2 hours. The reaction solution obtained by the modification reaction was centrifuged to obtain a solid, and the obtained solid was dried at 60°C for 12 hours to obtain modified calcium carbonate.

[0051] Example 2

[0052] Modified calcium carbonate was prepared according to the method of Example 1, except that the amount of silane coupling agent KH-580 was changed to 2% of the mass of ethanol.

[0053] Example 3

[0054] Modified calcium carbonate was prepared according to the method of Example 1, except that the amount of silane coupling agent KH-580 was changed to 3% of the mass of ethanol.

[0055] Example 4

[0056] Modified calcium carbonate was prepared according to the method of Example 1, except that the amount of silane coupling agent KH-580 was changed to 4% of the mass of ethanol.

[0057] Example 5

[0058] Modified calcium carbonate was prepared according to the method of Example 1, except that the amount of silane coupling agent KH-580 was changed to 5% of the mass of ethanol.

[0059] Example 6

[0060] Modified calcium carbonate was prepared according to the method of Example 1, except that the cubic calcium carbonate was replaced by rod-shaped calcium carbonate (aragonite phase crystal type, with an average particle size of 5.82 μm).

[0061] Example 7

[0062] Modified calcium carbonate was prepared according to the method of Example 4, except that the amount of silane coupling agent KH-580 was changed to 2% of the mass of ethanol.

[0063] Example 8

[0064] Modified calcium carbonate was prepared according to the method of Example 4, except that the amount of silane coupling agent KH-580 was changed to 3% of the mass of ethanol.

[0065] Example 9

[0066] Modified calcium carbonate was prepared according to the method of Example 4, except that the amount of silane coupling agent KH-580 was changed to 4% of the mass of ethanol.

[0067] Example 10

[0068] Modified calcium carbonate was prepared according to the method of Example 4, except that the amount of silane coupling agent KH-580 was changed to 5% of the mass of ethanol.

[0069] Embodiment 11

[0070] Modified calcium carbonate was prepared according to the method of Example 4, except that the modification reaction time was changed to 0.5 h.

[0071] Example 12

[0072] Modified calcium carbonate was prepared according to the method of Example 4, except that the modification reaction time was changed to 1 h.

[0073] Embodiment 13

[0074] Modified calcium carbonate was prepared according to the method of Example 4, except that the modification reaction time was changed to 1.5 h.

[0075] Embodiment 14

[0076] Modified calcium carbonate was prepared according to the method of Example 4, except that the modification reaction time was changed to 2.5 h.

[0077] Embodiment 15

[0078] Modified calcium carbonate was prepared according to the method of Example 9, except that the modification reaction time was changed to 0.5 h.

[0079] Example 16

[0080] Modified calcium carbonate was prepared according to the method of Example 9, except that the modification reaction time was changed to 1 h.

[0081] Embodiment 17

[0082] Modified calcium carbonate was prepared according to the method of Example 9, except that the modification reaction time was changed to 1.5 h.

[0083] Embodiment 18

[0084] Modified calcium carbonate was prepared according to the method of Example 9, except that the modification reaction time was changed to 2.5 h.

[0085] Comparative Example 1

[0086] Modified calcium carbonate was prepared according to the method of Example 4, except that the silane coupling agent KH-580 was replaced by the silane coupling agent KH-570 (γ-methacryloxypropyltrimethoxysilane).

[0087] Comparative Example 2

[0088] Modified calcium carbonate was prepared according to the method of Comparative Example 2, except that the cubic calcium carbonate was replaced by rod-shaped calcium carbonate (aragonite phase crystal type, with an average particle size of 5.82 μm).

[0089] Characterization of modified calcium carbonate

[0090] 1. Contact angle

[0091] The contact angles of cubic calcium carbonate, rod-shaped calcium carbonate, and the modified calcium carbonate obtained in Examples 1-18 and Comparative Examples 1-2 with water were tested. The results are shown in Table 1 below.

[0092] Table 1 Contact angles of cubic calcium carbonate, rod-shaped calcium carbonate, and modified calcium carbonate obtained in Examples and Comparative Examples with water

[0093]

[0094] As can be seen from Table 1, the hydrophobicity of the modified calcium carbonate obtained by the modification method of the present invention is improved, and the contact angle with water can reach more than 120°, while the contact angle with water of the modified calcium carbonate obtained in Comparative Examples 1-2 is 0°. The above test results show that the hydrophobicity of the modified calcium carbonate obtained by the modification method of calcium carbonate provided by the present invention is effectively improved.

[0095] 2. SEM characterization

[0096] The morphology of the calcium carbonate used in Examples 1-18 and Comparative Examples 1-2 and the obtained modified calcium carbonate was characterized using a scanning electron microscope (SEM). Figure 1-3 shown.

[0097] Figure 1 It is a comparison of SEM images of cubic calcium carbonate, rod-shaped calcium carbonate, the modified calcium carbonate obtained in Example 4, the modified calcium carbonate obtained in Example 9, and the modified calcium carbonate obtained in Comparative Examples 1-2, wherein a to f are respectively the SEM image of cubic calcium carbonate, the SEM image of the modified calcium carbonate obtained in Comparative Example 1, the SEM image of the modified calcium carbonate obtained in Example 4, the SEM image of rod-shaped calcium carbonate, the SEM image of the modified calcium carbonate obtained in Comparative Example 2, and the SEM image of the modified calcium carbonate obtained in Example 9. As shown in a, the morphology of cubic calcium carbonate is mainly irregular cubes, and the particle sizes are different. The average particle size is 2.75μm measured by scanning electron microscopy; as shown in b, the calcium carbonate modified by silane coupling agent KH570 is still mainly irregular cubes, and some porous fine particles are attached to the smooth particle surface, which can increase the surface roughness and reduce the particle size of the cubic particles. The average particle size is 1.91μm after testing; as shown in c, the calcium carbonate modified by silane coupling agent KH580 is irregular in shape, and some irregular shapes are caused by the aggregation of cubic calcium carbonate. It can be observed The surface of irregular calcium carbonate is rough and porous, and the average particle size (i.e., average length) is 5.31 μm as tested by scanning electron microscopy; as shown in d, the morphology of rod-shaped calcium carbonate is mainly rod-shaped, with thick rods in the middle and thin rods at both ends, and the average particle size is 5.82 μm; as shown in e, the rod-shaped calcium carbonate modified by silane coupling agent KH570 is mainly short rod-shaped, and small and irregular particles are attached to the surface of some short rods, and the average particle size of the short rods is 3.43 μm; as shown in f, the rod-shaped calcium carbonate modified by silane coupling agent KH580 is rod-shaped aggregated spherical, with a rough and porous surface and an average particle size of 6.32 μm. From the above characterization, it can be seen that the morphology of the two crystal forms of calcium carbonate after modification by silane coupling agent KH570 has not changed, the average particle size has decreased, particles are attached to the surface of some particles, and the surface roughness has increased; after modification by silane coupling agent KH580, the two crystal forms of calcium carbonate are in an aggregated state.

[0098] Figure 2The SEM images of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 1-10, wherein af are SEM images of cubic calcium carbonate and modified calcium carbonate obtained in Examples 1-5, and gl are SEM images of rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 6-10. As shown in af, with the increase in the amount of silane coupling agent KH580, rough porous granular substances are attached to the surface of some cubes. When the amount of silane coupling agent KH580 is increased to 4% of the mass of ethanol, the cubes gradually aggregate, and a layer of "mud"-like substances is attached to the surface of the cubes, and almost all of them are covered by it, and the surface is getting rougher and rougher. As shown in gl, with the increase in the amount of silane coupling agent KH580, small particles are attached to the surface of rod-shaped calcium carbonate and between the rods, and gradually increase. When the amount of silane coupling agent KH580 is increased to 4%, the rods gradually aggregate, and are spherical, and as the content increases, the spheres gradually become larger, and the surface is getting rougher and rougher.

[0099] Figure 3 It is the SEM image of cubic calcium carbonate, rod-shaped calcium carbonate, modified calcium carbonate obtained in Example 4, modified calcium carbonate obtained in Example 9, and modified calcium carbonate obtained in Example 11-18. Wherein af is the SEM image of cubic calcium carbonate, modified calcium carbonate obtained in Example 11-13, modified calcium carbonate obtained in Example 4, and modified calcium carbonate obtained in Example 14, i.e., in the order of modification reaction time 0, 0.5h, 1h, 1.5h, 2.0h, and 2.5h. As shown in af, for the modification of cubic calcium carbonate, as the modification time is prolonged, the surface attachments of the cube are increasing, indicating that the surface of the cubic calcium carbonate is becoming more and more rough. G1 is the SEM image of rod-shaped calcium carbonate, modified calcium carbonate obtained in Example 15-17, modified calcium carbonate obtained in Example 9, and modified calcium carbonate obtained in Example 18, i.e., in the order of modification reaction time 0, 0.5h, 1h, 1.5h, 2.0h, and 2.5h. As shown in gl, for the modification of rod-shaped calcium carbonate, as time goes by, the length of the rod-shaped calcium carbonate rods becomes shorter and shorter, and they gradually gather together, similar to a "sugar melon" (see i); from Figures j to l, it can be observed that as the modification time continues to increase, the rod-shaped calcium carbonate gradually gathers into balls (see j), and the longer the time, the larger the ball and the rougher the surface.

[0100] 3. X-ray diffraction (XRD) characterization

[0101] XRD characterization was performed on cubic calcium carbonate, rod-shaped calcium carbonate, the modified calcium carbonate obtained in Example 4, the modified calcium carbonate obtained in Example 9, and the modified calcium carbonate obtained in Comparative Examples 1-2 to test their crystal forms. Figure 4As shown in the figure, a is the XRD pattern of cubic calcium carbonate, the modified calcium carbonate obtained in Example 4 and the calcium carbonate obtained in Comparative Example 1, and b is the XRD pattern of rod-shaped calcium carbonate, the modified calcium carbonate obtained in Example 9 and the calcium carbonate obtained in Comparative Example 2. As shown in a, the modification of the silane coupling agent KH580 does not change the crystal form of cubic calcium carbonate, which is calcite-type; as shown in b, the modification of the silane coupling agent KH580 does not change the crystal form of rod-shaped calcium carbonate, which is mainly calcite-type and aragonite-type. It can be seen that the modification of the silane coupling agent KH580 does not change the crystal form of calcium carbonate.

[0102] 4. Infrared spectroscopy (FT-IR) analysis

[0103] The structures of cubic calcium carbonate, rod-shaped calcium carbonate, modified calcium carbonate obtained in Example 4, modified calcium carbonate obtained in Example 9 and modified calcium carbonate obtained in Comparative Examples 1-2 were characterized using an infrared spectrometer. Figure 5 As shown in a, a is the FT-IR spectra of cubic calcium carbonate, the modified calcium carbonate obtained in Example 4, and the calcium carbonate obtained in Comparative Example 1, and b is the FT-IR spectra of rod-shaped calcium carbonate, the modified calcium carbonate obtained in Example 9, and the calcium carbonate obtained in Comparative Example 2. As shown in a, 710 cm -1 、872cm -1 、1424cm -1 The characteristic absorption peaks of calcite-type calcium carbonate appear at 2- Antisymmetric stretching vibration, symmetric stretching vibration and in-plane bending vibration peaks; 2800~3000cm -1 Broad absorption peaks appeared in the range of 2972 ​​cm-1 and 2972 ​​cm-2 after modification of KH570 and KH580. -1 A weak characteristic peak appeared at 1135cm, indicating that KH570 and KH580 were hydrolyzed in the alcohol aqueous solution, and the ethoxy groups were converted into hydroxyl groups. Therefore, the number of hydroxyl groups on the surface of the modified calcium carbonate was larger. The KH580-modified calcium carbonate had a peak at 1135cm -1 and 1015cm -1 The new absorption peak at 710 cm is the stretching vibration peak of the -Si-O- group. After KH570 modification, calcium carbonate did not show an absorption peak here, indicating that KH580 was successfully grafted on the surface of calcium carbonate, but KH570 was not successfully grafted. As shown in b, 710 cm -1 、872cm -1 、1082cm -1 、1493cm -1 The characteristic absorption peaks of calcium carbonate appear at 2- The antisymmetric stretching vibration, symmetric stretching vibration, out-of-plane bending vibration and in-plane bending vibration peaks of aragonite calcium carbonate, 1082cm -1Characteristic absorption peaks appear at 1493cm -1 The characteristic peak at 2800-3000cm -1 A broad absorption peak appears in the range of 2914 cm-1. The rod-shaped calcium carbonate modified by KH570 and KH580 has a peak at 2914 cm-1. -1 The peak at 1139cm -1 and 1013cm -1 New absorption peaks appeared at these two locations, while the rod-shaped calcium carbonate modified by KH570 did not show absorption peaks at these two locations, indicating that KH580 and the hydroxyl groups adsorbed on the surface of the rod-shaped calcium carbonate were dehydrated in the solvent to form a chemical connection to form long chains such as -Si-O-calcium carbonate, while KH570 was not successfully grafted.

[0104] 5. Hydrophilicity and lipophilicity test

[0105] (1) Activation index

[0106] The activation index of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 1-20 was tested by the following method:

[0107] Weigh 0.5 g of the test substance (recorded as m1) and place it in 200 mL of distilled water. Stir it electrically at 40°C for 30 min, then let it stand for 2 h. Scrape off the floating matter on the water surface, filter the sediment, and wash it with ethanol. Dry the washed sediment at 60°C for 4 h. Weigh the mass of the dried sediment and record it as m2. Calculate the activation index R of the sample, as shown in formula (1).

[0108]

[0109] like Figure 6 The activation indexes of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 1-10 are shown, wherein when the amount of silane coupling agent is 0, it corresponds to the activation index of cubic calcium carbonate and rod-shaped calcium carbonate, and when the amount of silane coupling agent is 1%, 2%, 3%, 4% and 5%, it corresponds to the modified calcium carbonate obtained in Examples 1-10 using the corresponding amount of silane coupling agent. Figure 6 It can be seen that with the increase in the amount of silane coupling agent KH580, the activation index of the modified calcium carbonate first increases sharply and then decreases slowly. When the amount of silane coupling agent reaches 4%, the activation indexes of the two modified crystalline calcium carbonates (modified calcium carbonates obtained in Examples 4 and 9) reach the maximum value.

[0110] like Figure 7The figure shows the activation index of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 4, 9 and 11-18, wherein the activation index of cubic calcium carbonate and rod-shaped calcium carbonate corresponds to the activation index of modified calcium carbonate when the modification time is 0h, 1.0h, 2.0h and 2.5h, respectively, corresponding to the modified calcium carbonate obtained in the examples with the corresponding modification time. Figure 7 It can be seen that as the modification time is extended to 2h, the activation index of the two crystalline calcium carbonates reaches the maximum value, but as the time continues to extend, the activation index decreases slightly.

[0111] (2) Oil absorption value

[0112] The oil absorption values ​​of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 1-20 to organic matter (edible oil, petroleum ether and dichloromethane) were tested by the following method:

[0113] Weigh 0.2 g of the substance to be tested (recorded as m3) and place it on a watch glass. Add organic matter dropwise until all the substances to be tested are aggregated into a mass. Weigh the total mass, recorded as m4, and calculate the oil absorption value H according to the following formula (2).

[0114]

[0115] like Figure 8 The oil absorption values ​​of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 1-10 are shown, wherein a is the oil absorption value of cubic calcium carbonate (abbreviated as calcium carbonate) and modified calcium carbonate obtained in Examples 1-5, b is the oil absorption value of rod-shaped calcium carbonate (abbreviated as calcium carbonate) and modified calcium carbonate obtained in Examples 6-10, and the amount of silane coupling agent used in the figure corresponds to the example using the corresponding amount of KH580. Figure 8 It can be seen that for the two calcium carbonates, as the amount of KH580 increases, their oil absorption values ​​change to varying degrees. When the amount reaches 4%, the oil absorption value is the largest.

[0116] like Fig. 9 The oil absorption values ​​of cubic calcium carbonate, rod-shaped calcium carbonate and modified calcium carbonate obtained in Examples 4, 9 and 11-18 are shown, wherein the activation index of cubic calcium carbonate and rod-shaped calcium carbonate corresponds to the modification time of 0, and the activation index of modified calcium carbonate obtained in Examples with the corresponding modification time corresponds to the modification time of 0.5h, 1.0h, 2.0h and 2.5h. Fig. 9 It can be seen that with the extension of the modification reaction time, the oil absorption value of the modified calcium carbonate changes to varying degrees. The longer the modification reaction time, the greater the oil absorption value, and the modification time is 2.0h-2.5h, and it hardly changes. It can be seen that the hydrophobicity and lipophilicity of the two crystalline calcium carbonates are the best when the modification time reaches 2h.

[0117] Embodiment 19

[0118] n-Hexane (10 g) and PDMS (0.5 g) were mixed in a mass ratio of 20:1, and then 0.2 g of the modified calcium carbonate obtained in step (1) of Example 4 was added (the mass ratio of modified calcium carbonate to PDMS was 2:5), and magnetic stirring was performed for 10 min to obtain a second mixed solution.

[0119] The glass slide was immersed in the second mixed solution and then taken out, and then dried at room temperature (24 h), forming a super hydrophobic coating with a thickness of 0.1 mm on the surface of the glass substrate.

[0120] Examples 20-22

[0121] The amount of modified calcium carbonate was changed so that the mass ratio of modified calcium carbonate to PDMS was 4:5, 6:5 and 8:5, respectively, to prepare super-hydrophobic coatings as Examples 20-22.

[0122] Examples 23-26

[0123] Super hydrophobic coatings were prepared according to Examples 19-22, respectively, as Examples 23-26, except that the modified calcium carbonate was replaced by the modified calcium carbonate obtained in Example 9.

[0124] Comparative Example 3

[0125] The PMDS is dissolved in a n-hexane solution, then formed into a film, and dried to obtain a PMDS hydrophobic layer.

[0126] Characterization of superhydrophobic coatings

[0127] 1. Contact angle

[0128] The contact angles of the super hydrophobic coatings obtained in Examples 19-26 and the PMDS hydrophobic layer obtained in Comparative Example 3 with water were tested, and the results are shown in Table 2.

[0129] Table 2 Contact angles of the super hydrophobic coatings obtained in Examples 19-26 and the PMDS hydrophobic layer obtained in Comparative Example 3

[0130] Example Comparative Example 3 Embodiment 19 Embodiment 20 Embodiment 21 Embodiment 22 Contact Angle 117.98° 130.44° 158.71° 155.32° 143.75° Example — Embodiment 23 Embodiment 24 Embodiment 25 Embodiment 26 Contact Angle — 134.60° 146.27° 157.69° 143.49°

[0131] As can be seen from Table 2, the hydrophobicity of the super hydrophobic coating provided by the present invention is much better than that of the PMDS hydrophobic layer, and the contact angle of the super hydrophobic coating can reach more than 150°.

[0132] 2. Self-cleaning ability test

[0133] The self-cleaning ability of the coatings obtained in Examples 20 and 25 and the coating obtained in Comparative Example 3 was tested by the following method:

[0134] Take the methylene blue solution as the pollutant, place the coated slide glass obliquely against the container wall of the watch glass with the coating side facing up, drop the methylene blue solution on the coating, observe the methylene blue solution sliding into the watch glass, then wipe the surface of the slide glass with a paper towel and observe the contamination on the surface of the paper towel.

[0135] The above method was used to test the self-cleaning ability of the slide as a control. The test results are as follows Fig.10 As shown, group a (a1-a3), group b (b1-b3), group c (c1-c3) and group d (d1-d3) correspond to the self-cleaning effect diagrams of the glass slide, the hydrophobic coating obtained in comparative example 3, the super hydrophobic coating obtained in example 20 and the super hydrophobic coating obtained in example 25, respectively. a1, b1, c1 and d1 are the conditions of the methylene blue solution dripping, a2, b2, c2 and d2 are the surface conditions of the coating after wiping with a paper towel, and a2, b2, c2 and d2 are the surface conditions of the paper towel after wiping with a paper towel. By Fig.10 It can be seen that the super-hydrophobic coating provided by the present invention has a better self-cleaning ability than the glass slide and the PDMS hydrophobic coating. After the methylene blue solution flows through the surface of the super-hydrophobic coating, it basically does not leave any traces on the surface of the super-hydrophobic coating, which means that it has a better self-cleaning ability.

[0136] The self-cleaning ability of the super-hydrophobic coatings of other embodiments was tested, and similar results were obtained.

[0137] While preferred embodiments of the present invention have been shown and described, it is contemplated that those skilled in the art may devise various modifications of the present invention within the spirit and scope of the appended claims.

Claims

1. A method for modifying calcium carbonate, comprising the following steps: Calcium carbonate, γ-mercaptopropyltriethoxysilane and ethanol are mixed, and then ammonia water is added to carry out a modification reaction to obtain modified calcium carbonate.

2. The modification method according to claim 1, characterized in that: The calcium carbonate is at least one of cubic calcium carbonate and rod-shaped calcium carbonate, and the average particle size of the calcium carbonate is 2.5-6.0 μm.

3. The modification method according to claim 1 or 2, characterized in that: The mass ratio of the calcium carbonate to the ethanol is 1:16-18, and the mass of the γ-mercaptopropyltriethoxysilane is 1-5% of the mass of the ethanol.

4. The modification method according to claim 1 or 2, characterized in that: The concentration of the ammonia water is 13-14 mol / L, the mass volume ratio of the calcium carbonate to the ammonia water is 1 g:14-16 mL, and the ammonia water is added at a speed of 1.2-1.8 mL / min.

5. The modification method according to claim 1 or 2, characterized in that: The modification reaction temperature is 45-55°C and the reaction time is 0.5-2.5h.

6. The modification method according to claim 1 or 2, characterized in that: After the modification reaction, the method further includes performing solid-liquid separation on the reaction liquid obtained from the modification reaction, and drying the obtained solid, and the obtained dried solid is the modified calcium carbonate.

7. A super-hydrophobic coating comprising a polymer matrix and modified calcium carbonate obtained by the modification method described in any one of claims 1 to 6.

8. The super hydrophobic coating according to claim 7, characterized in that The mass ratio of the modified calcium carbonate to the polymer matrix is ​​2-8:5, and the polymer matrix is ​​polydimethylsiloxane.

9. A method for preparing a super-hydrophobic coating according to claim 7 or 8, comprising the following steps: The modified calcium carbonate, the polymer matrix and the organic solvent are mixed to obtain a mixed solution, The mixed solution is formed into a film and then dried to obtain a super hydrophobic coating.

10. The preparation method according to claim 9, characterized in that: The mass ratio of the polymer matrix to the organic solvent is 1:17-23, and the organic solvent is n-hexane.

Citation Information

Cited By

  • Antirust material with hydrophobicity and easy dispersibility, coating and preparation method

    CN122168062A

  • Polyacrylate / CaCO3 superhydrophobic self-cleaning coating, coating material and preparation method of coating material

    CN122917620A